Legal geographies and political ecologies of water allocation in Maui, Hawai'i. Issue 110 (March 2020) - Cantor, Alida; Kay, Kelly; Knudson, Chris
Highlights: Hawai'i's sugar industry has diverted water from traditional and ecological uses. Hawaiian activists and lawyers have used legal tools to reclaim instream flows. Legal geography and political ecology help understand socioenvironmental change. Legal processes are plural and develop in place-specific ways. Legal processes and socioenvironmental change are inextricable and power-laden. Abstract: Throughout the Hawaiian Islands, sugar plantations have controlled a large proportion of water resources for over a century, often leaving little water in streams to support ecosystems or Native Hawaiian cultural and agricultural practices. Recently, in Maui, Hawai'i, community activists and lawyers representing Native Hawaiian and environmental interests have successfully reclaimed water resources for instream flow utilizing legal processes and tools such as Hawai'i's public trust doctrine, which has plural roots in both Hawaiian and Western legal traditions. In this paper, we use qualitative fieldwork, including interviews, participant observation, and archival data collection, to explore two recent and ongoing legal cases around water allocation in Maui: Nā Wai 'Ehā and East Maui. The research uses legal geography and political ecology to examine the use of the public trust doctrine in challenging water allocation practices in Maui, specifically focusing on the concepts of legal pluralism and socioenvironmental hybridity. We examine the ways in which plural legal processes and precedents have developed and combined in place-specific ways, and connect legal pluralism with ideas of hybridity from nature-society geography. In keeping with the goals of political ecology, the paper examines legal processes and socioenvironmental change as inextricable and power-laden. We demonstrate that the intersection of legal geography with political ecology can contribute a stronger understanding of the context-specific dynamics of socioenvironmental change.